"Human content" of Roman law - Гуренко-Вайцман, Марина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
Scientific review of the monograph of V. M. Volk "The bivalence of Roman legal reality".